Resin composition, preparation method thereof, light-cured resin and application
By adding silane modified filler to the resin composition, the problem of insufficient wear resistance of the photocured resin is solved, and high wear resistance and hardness and bending strength suitable for dental materials are achieved.
Patent Information
- Application Number
- CN202411940248.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The existing photocuring resins are not able to resist wear during teeth chewing, resulting in long-term wear affecting the patient's chewing function and aesthetics.
By adding silane modified filler to the resin composition, the bonding between the filler and the resin matrix is enhanced, thereby improving the wear resistance of the resin.
It achieves high wear resistance of photocured resin, hardness ≧80 Shore D, wear height ≤450μm, bending strength above 80MPa, and suitable for dental materials.
Smart Images

Figure BDA0005212425180000101 
Figure BDA0005212425180000102 
Figure BDA0005212425180000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of resin compositions, and in particular to a resin composition and a preparation method thereof, a photocurable resin and applications thereof. Background Art
[0002] Resin restoration materials are increasingly favored by dentists and patients for their beauty and ease of operation. With the development of dental resin materials, people's attention to aesthetics has also increased. As a result, light-curing resins for personalized external dyeing of resin restorations have emerged and are widely used. The dentures after external dyeing more realistically simulate the appearance and color of natural teeth, making the restoration results more natural and beautiful. Light-curing resins can perfectly restore the original shape of teeth for patients. Their color is very close to that of natural teeth, the surface is smooth, and the traces of restoration are almost undetectable. At the same time, the operation process of light-curing resins is simple and quick for dentists, and the restoration work can be completed in a short time, improving efficiency.
[0003] During the oral chewing process, friction and wear are inevitable between teeth, teeth and restorations, restorations and restorations, and between them and food. Friction and wear is a complex process. Photocurable resins with poor wear resistance will inevitably affect the patient's chewing function and appearance after long-term wear. Therefore, it is urgent to develop a photocurable resin with high wear resistance to cope with the wear caused by tooth chewing.
[0004] Studies have shown that when composite resins are subjected to chewing forces, due to the large difference in elastic modulus between the matrix and filler, stress is mainly transmitted through the matrix with a smaller elastic modulus. Therefore, during the friction and wear process, wear begins with the matrix, followed by the exposure and shedding of the filler, and stress concentration is more likely to occur around the filler particles, which accelerates the loosening of particles and the exposure of new matrix, making the surface rough and the wear resistance reduced. This cycle repeats itself, so the filler affects the wear resistance of the composite. Studies have found that harder fillers exhibit better wear resistance; and in the same filler system, the resin composite with ultrafine fillers exhibits better wear resistance because the filler volume is small, the distance between fillers is small, the matrix exposed to the friction and wear surface is small, and the unit area of the filler particles and the friction counterface increases, thereby improving the wear resistance of the material.
[0005] Japanese Patent Application Publication No. 4-29910 discloses a photopolymerizable dental surface coating material composed of a photopolymerizable dental surface coating material. However, this conventional dental photopolymerizable surface coating material has insufficient wear resistance and will wear out in a short period of time during brushing, affecting the appearance.
[0006] Therefore, there is a need to develop more wear-resistant dental materials. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a resin composition and a preparation method thereof, a photocurable resin and an application thereof. By adding a silane-modified filler to the resin composition, the bonding degree between the filler and the resin matrix is enhanced, thereby increasing the wear resistance.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a resin composition, which comprises, in terms of mass fraction: at least two polymerizable acrylate derivatives; at least one acrylate monomer; at least one photoinitiator; at least two fillers; the filler is a silane-modified filler; based on 100 parts by mass of the resin composition, the mass fraction of the filler is 2 to 30 parts.
[0010] It is worth noting that in order to ensure good fluidity and photopolymerization, only a very small amount of fumed silica (generally 0.5% to 2%) is added to the photocurable resin dyeing liquid used for personalized dyeing of resin restorations, which makes the wear resistance of the photocurable resin very poor. In the oral environment, it will gradually wear and fall off as the teeth chew, affecting the appearance. Fillers are added to the resin composition provided by the present invention. The filler itself has a higher hardness than the resin, which can increase the hardness of the cured resin, thereby improving the wear resistance; however, due to the difference between the filler and the resin material, the bonding force between the filler and the resin is poor. Therefore, the present invention adopts a filler after silane modification of the filler. This silane-modified filler can improve the bonding effect between the filler and the resin matrix, thereby making the surface rough and increasing the wear resistance.
[0011] Specifically, the mass fraction of the filler can be, for example, 2 parts, 6 parts, 9 parts, 12 parts, 15 parts, 18 parts, 21 parts, 24 parts, 27 parts or 30 parts, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0012] Preferably, the polymerizable acrylate derivative has any one or a combination of at least two of hydroxyl, amino or isocyanate groups, wherein typical but non-limiting combinations are a combination of hydroxyl and amino groups, a combination of isocyanate and amino groups, and a combination of hydroxyl and isocyanate groups.
[0013] The present invention preferably uses polymerizable acrylate derivatives having the above-mentioned groups, which have good reactivity in the resin and can improve the crosslinking density and mechanical properties of the resin.
[0014] Preferably, the polymerizable acrylate derivative comprises at least one of bisphenol A glycerol dimethacrylate (Bis-GMA), triethylene glycol dimethacrylate (TEGDMA), urethane dimethacrylate (UDMA), mercapto-modified acrylate (8630), trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), ditrimethylolpropane tetraacrylate (DI-TMPTA), pentaerythritol triacrylate (PETA), propoxylated glycerol triacrylate (GPTA), tris(2-hydroxyethyl)isocyanuric acid triacrylate (THEICTA), trimethylolpropane triacrylate (DTMPTTA), pentaerythritol tetraacrylate (PETTA), (4-ethoxy)pentaerythritol tetraacrylate (PE(EO)4TTA) or dipentaerythritol hexaacrylate (DPHA). A combination of two or more, wherein a typical but non-limiting combination is a combination of mercapto-modified acrylate (8630), trimethylolpropane triacrylate (TMPTA) and ditrimethylolpropane tetraacrylate (DI-TMPTA), a combination of bisphenol A glycerol dimethacrylate (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA), a combination of pentaerythritol tetraacrylate (PETTA) and triethylene glycol dimethacrylate (TEGDMA), a combination of bisphenol A glycerol dimethacrylate (Bis-GMA) and pentaerythritol tetraacrylate (PETTA), a combination of dipentaerythritol hexaacrylate (DPHA) and triethylene glycol dimethacrylate (TEGDMA), preferably a combination of at least two of Bis-GMA, TEGDMA or UDMA, preferably a combination of the three, has better wear resistance and polymerization effect.
[0015] When the present invention adopts a combination of Bis-GMA, TEGDMA and UDMA, it is preferably controlled that the mass ratio of Bis-GMA, TEGDMA and UDMA is (0.5-4):(0.5-2):1, wherein the number of Bis-GMA can be, for example, 0.5, 1, 1.2, 1.5, 1.8, 2.0, 2.2, 2.5, 2.8, 3.0, 3.2, 3.5, 3.8 or 4.0, etc.; the number of TEGDMA can be, for example, 0.5, 1, 1.2, 1.5, 1.8, 2.0, 2.2, 2.5, 2.8, 3.0, 3.2, 3.5, 3.8 or 4.0, etc.
[0016] Preferably, the acrylate monomer includes any one or a combination of at least two of N-butyl (meta) acrylate, N-propyl (meta) acrylate, isopropyl (meth) acrylate, tert-butyl (meth) acrylate, cyclohexyl (meth) acrylate, tert-butyl cyclohexyl (meth) acrylate, isobutyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, isodecene (meth) acrylate, laurel (meth) acrylate or stearyl (meth) acrylate, wherein a typical but non-limiting combination is a combination of N-butyl (meta) acrylate and N-propyl (meta) acrylate, a combination of tert-butyl (meth) acrylate and N-propyl (meta) acrylate, a combination of N-butyl (meta) acrylate and tert-butyl (meth) acrylate, a combination of isodecene (meth) acrylate and N-propyl (meta) acrylate, a combination of stearyl (meth) acrylate and stearyl (meth) acrylate, preferably methyl methacrylate (MMA).
[0017] Preferably, in terms of mass percentage, the resin composition comprises 50 to 70 parts of a polymerizable acrylate derivative, 10 to 30 parts of an acrylate monomer, 1 to 5 parts of a photoinitiator, and 2 to 30 parts of a filler. Among them, the polymerizable acrylate derivative is 50-70 parts, for example, it can be 50 parts, 53 parts, 55 parts, 57 parts, 59 parts, 62 parts, 64 parts, 66 parts, 68 parts or 70 parts, but it is not limited to the listed values, and other values not listed in the range are equally applicable; the acrylate monomer is 10-30 parts, for example, it can be 10 parts, 13 parts, 15 parts, 17 parts, 19 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, but it is not limited to the listed values, and other values not listed in the range are equally applicable; the photoinitiator is 1-5 parts, for example, it can be 1 part, 1.5 parts, 1.9 parts, 2.4 parts, 2.8 parts, 3.3 parts, 3.7 parts, 4.2 parts, 4.6 parts or 5 parts, but it is not limited to the listed values, and other values not listed in the range are equally applicable.
[0018] Preferably, the filler in the silane-modified filler includes an organic filler and / or an inorganic filler.
[0019] Preferably, the organic filler comprises any one of regenerated cellulose, polyamide fiber, polymethyl methacrylate microspheres or ultra-high molecular weight polyethylene powder, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of polyamide fiber and polymethyl methacrylate microspheres, a combination of ultra-high molecular weight polyethylene powder and polymethyl methacrylate microspheres, and a combination of polyamide fiber and ultra-high molecular weight polyethylene powder.
[0020] Preferably, the inorganic filler comprises fumed silica and / or glass powder.
[0021] Preferably, the glass powder comprises any one of quartz, glass ceramic or radiopaque glass powder or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of quartz and glass ceramic, a combination of radiopaque glass powder and glass ceramic, and a combination of quartz and radiopaque glass powder.
[0022] The preferred filler of the present invention is a combination of glass powder and fumed silica. When the combination of the two is used, the mass ratio of the glass powder to the fumed silica is (0.1-10):1, for example, it can be 0.1:1, 1.2:1, 2.3:1, 3.4:1, 4.5:1, 5.6:1, 6.7:1, 7.8:1, 8.9:1 or 10:1, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0023] Preferably, the particle size of the filler is 0.01-1 μm, for example, it can be 0.01 μm, 0.12 μm, 0.23 μm, 0.34 μm, 0.45 μm, 0.56 μm, 0.67 μm, 0.78 μm, 0.89 μm or 1 μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0024] Preferably, the resin composition further comprises at least one additive.
[0025] Preferably, the additive comprises any one of a co-initiator, a colorant or a defoamer or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of a co-initiator and a colorant, a combination of a defoamer and a colorant, and a combination of a co-initiator and a defoamer.
[0026] The present invention has no special restrictions on the co-initiator, colorant or defoamer in the above resin composition. Any material known to those skilled in the art that can be used for the co-initiator, colorant or defoamer can be used, and can also be adjusted according to the actual process.
[0027] Preferably, the resin composition includes 1 to 10 parts of additives in terms of mass percentage, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0028] Preferably, the molar extinction coefficient of the photoinitiator at 365 nm or 405 nm is greater than 1000, for example, it can be 1001, 1050, 1060, 1080, 1100, 1150, 1200, 1250, 1300, 1400 or 1500, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0029] Preferably, the photoinitiator comprises any one or a combination of at least two of camphorquinone (CQ), 9,10-phenanthrenequinone, 1-phenylpropane-1,2-dione, 2,2-dimethoxy-2-phenylacetophenone (DMPA), diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide (TPO), 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide (TMO), dibenzoyldiethylgermane, tetrabenzoylgermane, tetra(o-methylbenzoyl)germane or tetra(acyl)stannane. Combinations, wherein typical but non-limiting combinations are a combination of camphorquinone (CQ) and 9,10-phenanthrenequinone, a combination of 1-phenylpropane-1,2-dione and 9,10-phenanthrenequinone, a combination of camphorquinone (CQ) and 2,2-dimethoxy-2-phenylacetophenone (DMPA), a combination of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide (TPO) and 9,10-phenanthrenequinone, a combination of dibenzoyldiethylgermane and 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide (TMO).
[0030] In a second aspect, the present invention provides a method for preparing the resin composition described in the first aspect, the preparation method comprising: silane-modifying a filler to obtain a silane-modified filler; and mixing a polymerizable acrylate derivative, an acrylate monomer, a photoinitiator and the silane-modified filler to obtain a resin composition.
[0031] It is worth noting that those skilled in the art know that, during the preparation process, at least two polymerizable acrylate derivatives are first mixed evenly to obtain a resin system, and then the resin system is mixed with an acrylate monomer, a photoinitiator, a silane-modified filler and an additive, and stirred evenly to obtain a resin composition.
[0032] Preferably, the silane modification comprises: mixing a solvent, a filler and a silane coupling agent, and performing ultrasonic treatment, and then sequentially performing solid-liquid separation and drying to obtain the silane-modified filler.
[0033] Preferably, the power of the ultrasonic treatment is 100W to 500W, for example, it can be 100W, 145W, 189W, 234W, 278W, 323W, 367W, 412W, 456W or 500W, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0034] Preferably, the ultrasonic treatment time is 10 min to 60 min, for example, it can be 10 min, 16 min, 22 min, 27 min, 33 min, 38 min, 44 min, 49 min, 55 min or 60 min, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0035] Preferably, the temperature of the ultrasonic treatment is 20-80°C, for example, it can be 20°C, 27°C, 34°C, 40°C, 47°C, 54°C, 60°C, 67°C, 74°C or 80°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0036] Preferably, the solvent comprises ethanol and / or water.
[0037] Preferably, the silane coupling agent includes any one of γ-aminopropyl triethoxysilane, γ-(methacryloyloxy)propyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane or N-(β-aminoethyl)-γ-aminopropyl methyldimethoxysilane, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of γ-aminopropyl triethoxysilane and γ-(methacryloyloxy)propyl trimethoxysilane, a combination of γ-mercaptopropyl trimethoxysilane and γ-(methacryloyloxy)propyl trimethoxysilane, and a combination of γ-aminopropyl triethoxysilane and γ-mercaptopropyl trimethoxysilane.
[0038] Preferably, the silane coupling agent is 0.1% to 15% of the filler mass, for example, it can be 0.1%, 1.8%, 3.5%, 5.1%, 6.8%, 8.4%, 10.1%, 11.7%, 13.4% or 15%, etc., but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0039] In a third aspect, the present invention provides a photocurable resin, which is obtained by photocuring the resin composition described in the first aspect.
[0040] In a fourth aspect, the present invention provides a use of the resin composition of the first aspect in a dental material, or a use of the photocurable resin of the third aspect in a dental material.
[0041] Compared with the prior art, the present invention has at least the following beneficial effects:
[0042] (1) The resin composition provided by the present invention can obtain a photocurable resin with high wear resistance by using at least two polymerizable acrylate derivatives and silane-modified fillers, and the resin composition has good fluidity, a room temperature viscosity of ≤200 mPa·s, preferably ≤100 mPa·s, a leveling test preferably reaches Class A, and has excellent photopolymerization performance;
[0043] (2) The photocurable resin provided by the present invention has good wear resistance, hardness ≧80 Shore D, wear height ≤450 μm in abrasion test, preferably ≤425 μm, and bending strength above 80 MPa, and can be well applied in dental materials. DETAILED DESCRIPTION
[0044] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0045] The present invention has no special requirements for the specific selection of the colorant, and the colorant materials commonly used in dentistry can be selected according to the needs of teeth. In order to facilitate the comparison of the performance of the resin compositions in the following embodiments and comparative examples, Ivoclar Vivadent A1 is used as the added colorant, but it does not mean that the present invention can only use the above-mentioned colorant, and other colorants that can be used for dental resin compositions known to those skilled in the art can be used.
[0046] The preparation method of the resin composition provided in the following examples and comparative examples comprises the following steps:
[0047] A mixed solvent (ethanol and water volume ratio of 1.5:1), a filler and a silane coupling agent, and subjected to ultrasonic treatment at 200W for 20 minutes, and then centrifuged to remove the upper liquid phase and then take the lower solid phase for drying to obtain the silane-modified filler;
[0048] The colorant is diluted to a concentration of 2% and then used for standby; at least two polymerizable acrylate derivatives are firstly mixed evenly to obtain a resin system, and then the resin system is mixed with acrylate monomers, photoinitiators, silane-modified fillers and additives, and stirred evenly to obtain a resin composition.
[0049] The mass ratios of the silane coupling agents and the fillers used in Examples 1 to 6 are shown in Table 1.
[0050] Table 1
[0051]
[0052] The compositions and contents of the resin compositions of Examples 1 to 9 are shown in Tables 2 to 4.
[0053] Table 2
[0054]
[0055]
[0056] Table 3
[0057]
[0058] Table 4
[0059]
[0060]
[0061] The specific composition of the glass powder in Tables 1 to 4 is 15wt% of barium oxide (BaO), 15wt% of boron oxide (B2O3) and 65wt% of silicon dioxide (SiO2), and a small amount of 5wt% of aluminum oxide (Al2O3) is added. However, it does not mean that the present invention can only use the glass powder of the above composition, and other glass powders that are well known to those skilled in the art and can be applied to the resin composition are also applicable.
[0062] Example 10
[0063] This embodiment provides a resin composition, which is the same as that of Embodiment 1 except that UDMA is not added and the component amount of UDMA is distributed to Bis-GMA and TEGDMA according to the original ratio, and will not be described again.
[0064] During the polymerization process, the double bonds and other active groups in the molecular chain of UDMA can participate in the reaction, which can adjust the polymerization rate and cross-linking density, making the polymerization more uniform. When Bis-GMA and TEGDMA are used to replace UDMA, due to the relatively low reaction activity and large molecular volume of Bis-GMA, steric hindrance effects may occur during the polymerization process, affecting the uniformity of the polymerization reaction, causing the polymerization rate to be too fast, and causing stress concentration inside the material.
[0065] Embodiment 11
[0066] This embodiment provides a resin composition, which is the same as that of Embodiment 1 except that Bis-GMA is not added and the component amount of Bis-GMA is distributed to UDMA and TEGDMA according to the original ratio, and will not be described again.
[0067] Bis-GMA molecules are large and have a bisphenol A structure, which has a certain rigidity. When participating in polymerization, due to the relationship between molecular volume and structure, the polymerization network will have a certain spatial structure, which is conducive to the orderly arrangement and polymerization of other monomers around it. When there is no Bis-GMA and the amount of UDMA and TEGDMA is increased, there is no spatial structure regulation of Bis-GMA, and the arrangement and cross-linking of monomers during the polymerization process become disordered, resulting in poor uniformity of the polymerization network. In addition, TEGDMA and UDMA cannot make up for the loss of hardness and strength caused by the absence of Bis-GMA.
[0068] Example 12
[0069] This embodiment provides a resin composition, which is the same as that of Embodiment 1 except that TEGDMA is not added and the component amount of TEGDMA is distributed to UDMA and Bis-GMA according to the original ratio, and will not be described again.
[0070] TEGDMA is a low-viscosity monomer that mainly plays a diluting role in the system, which can effectively reduce the viscosity of the system and increase fluidity. When TEGDMA is not added and its components are distributed to UDMA and Bis-GMA, the viscosity of the system will increase significantly and the leveling property will be poor. TEGDMA helps to form a uniform cross-linked network structure because it can fill in the network gaps formed by other monomers, making the network more dense and uniform. Without TEGDMA, the network formed by UDMA and Bis-GMA will be uneven, and it is easy to have local excessive cross-linking and insufficient cross-linking in some areas.
[0071] Example 13
[0072] This embodiment provides a resin composition, which is the same as that of Embodiment 1 except that TEGDMA is replaced by an equal amount of PETA, and will not be described in detail here.
[0073] TEGDMA is a low molecular weight, bifunctional monomer with a short molecular chain and high double bond activity. It easily enters various parts of the polymerization system during the polymerization process, which helps to form a uniform cross-linked network structure. PETA, on the other hand, is a multifunctional monomer with three acrylate functional groups. It is more likely to undergo local cross-linking reactions during the polymerization process, resulting in a gel effect, which leads to a sharp increase in the viscosity of the system during the polymerization process. The diffusion of the monomer is restricted, which affects the full reaction of other monomers with PETA, resulting in uneven polymerization.
[0074] Embodiment 14
[0075] This embodiment provides a resin composition, which is the same as that of Embodiment 1 except that Bis-GMA is replaced by an equal amount of TMPTMA, and will not be described again.
[0076] When Bis-GMA is replaced by TMPTMA, the material loses its original toughness due to excessive rigidity. When subjected to external impact or bending, it is more prone to brittle fracture due to the lack of elastic deformation ability provided by the Bis-GMA structure.
[0077] Embodiment 15
[0078] This embodiment provides a resin composition, which is the same as that of Embodiment 5 except that the fumed silica is replaced by an equal amount of organic regenerated cellulose, and will not be described in detail here.
[0079] Compared with fumed silica, organic regenerated cellulose has lower strength and rigidity. As a fibrous material, it mainly plays a toughening role in the material. Compared with Example 1, the hardness of the resin composition is reduced, the wear resistance is slightly reduced, and the viscosity is increased, which affects the leveling property to a certain extent.
[0080] Example 16
[0081] This embodiment provides a resin composition, which is the same as that of Embodiment 5 except that the glass powder is replaced by an equal amount of organic regenerated cellulose, and will not be described again.
[0082] Glass powder has high hardness and rigidity, which can provide the material with good compression and deformation resistance and enhance structural stability. However, organic regenerated cellulose is a fiber structure, which provides certain support by interweaving and winding, and its strength is not as good as glass powder. Therefore, compared with Example 1, the hardness and flexural strength of the resin composition are reduced, and the wear height is increased accordingly. Since the fiber is not easy to disperse evenly, the viscosity increases, which affects the leveling property.
[0083] Comparative Example 1
[0084] This comparative example provides a resin composition, which is the same as Example 1 except that no fumed silica is added to the resin composition and the amount of the fumed silica component is distributed to the glass powder, and the rest is not repeated here.
[0085] Fumed silica plays a thixotropic and thickening role in the system. Nano-scale particles can form a three-dimensional network structure in the system to prevent the flow of the system. Without adding fumed silica, the viscosity of the resin composition decreases, which makes it easier to operate, but the hardness and flexural strength will be reduced, and the wear height will also increase.
[0086] Comparative Example 2
[0087] This comparative example provides a resin composition, which is the same as Example 1 except that no glass powder is added to the resin composition and the component amount of the glass powder is distributed to the fumed silica, and the rest is not repeated here.
[0088] Glass powder is a filling material that can effectively improve the hardness and rigidity of the material. The particles can be filled in the gaps to increase the density of the material, provide a supporting structure for the material, and are not easily deformed when subjected to external forces. Glass powder can improve the wear resistance of the material. Glass powder particles can form a wear-resistant layer on the surface of the material, which bears part of the friction and reduces the wear of the material. Therefore, if glass powder is not added, the hardness and flexural strength of the resin composition will be reduced, and the wear height will be significantly increased, thereby reducing the wear resistance of the photocurable resin.
[0089] Comparative Example 3
[0090] This comparative example provides a resin composition, which is the same as Example 1 except that glass powder and fumed silica are not added and the glass powder and fumed silica are proportionally distributed to other components, and the rest is not repeated here.
[0091] Comparative Example 4
[0092] This comparative example provides a resin composition, which is the same as Example 1 except that TEGDMA and UDMA are not added and the component amounts of TEGDMA and UDMA are distributed to Bis-GMA, and the rest are not repeated here.
[0093] Compared with Bis-GMA, TEGDMA and UDMA have lower viscosity and mainly play a diluting role in the system, which can reduce the viscosity of the liquid and increase fluidity. Bis-GMA has a large steric hindrance, and without the regulatory effect of TEGDMA and UDMA, the uniformity of the system will be affected, and local cross-linking will be excessive or uneven. Compared with Example 1, the hardness of the resin composition will increase, but the elastic modulus will decrease, and brittle fracture will occur easily. And the viscosity of the liquid will increase significantly, making it difficult to apply evenly during use, obvious brush marks, poor leveling, increasing the difficulty of operation, and affecting the aesthetics.
[0094] Comparative Example 5
[0095] This comparative example provides a resin composition, which is the same as Example 1 except that the amount of fumed silica and glass powder added is 0.5% respectively, and the amounts of other components are increased accordingly, and the rest are not repeated here.
[0096] Fumed silica and glass powder mainly play the role of enhancing mechanical properties. When the added amount is too small, the viscosity of the material will decrease and the fluidity will improve; however, the flexural strength and hardness of the material will decrease to varying degrees, and the wear height of the wear test will increase.
[0097] Comparative Example 6
[0098] This comparative example provides a resin composition, which is the same as Example 5 except that the amount of fumed silica and glass powder added is 20% respectively and the amounts of other components are reduced accordingly, and no further details are given here.
[0099] When too much fumed silica and glass powder are added, the viscosity of the resin composition will increase dramatically, resulting in poor leveling of the photocurable resin. When used for external dyeing of resin repair materials, there will be severe brush marks, affecting the aesthetics of the repair.
[0100] Performance Test:
[0101] 1. Wear test: According to the pharmaceutical industry standard of the People's Republic of China YY / T0113-2015 Wear resistance of composite resins in dentistry: Sample preparation: Fill the light-curing resin into a cylindrical mold (D=10mm, H=6mm) and place it in a light-curing light box for 5 minutes. After filling, place one end of the mold on a glass plate, cover it with a layer of plastic film, and cover it with a glass slide so that the upper and lower ends of the mold can remain parallel to each other. After the filling material is completely cured, remove the sample from the mold. Use a vernier caliper to measure and check whether the upper and lower ends of the specimen are completely parallel. If the two ends are not parallel, grind the sample with sandpaper until it is parallel. Before conducting friction and wear experiments, place all specimens in a water bath in (37±1)℃ distilled water for 24 hours.
[0102] The test method is to use a rubber plate as a counter-abrasive. The diameter of the rubber plate is (100±1) mm, the thickness is (6±0.2) mm, and the Shore hardness is 75±5. Fluorite powder and water are mixed into abrasives at a ratio of 100g:25g (abrasive particle size is 120-150 mesh, and the Shore hardness is 4). In the sandpaper pre-grinding experiment, 400-mesh water sandpaper is laid on the counter-abrasive, and then 25ml of distilled water is added to the material tray. The wear load is set to 22N and the number of frictions is set to 75 times. In the abrasive pre-grinding experiment and the formal wear experiment, the wear load is set to 172N and the number of abrasive pre-grinding is set to 150 times.
[0103] First, place 400-mesh water sandpaper in the material tray of the DMW-1 wear tester, add 25 ml of distilled water, pre-grind 75 times under the condition of abrasion load of 22 N, and then pre-grind 150 times with 125 g of uniformly prepared abrasive under the condition of abrasion load of 172 N. Remove the test piece and place it in a beaker filled with a neutral detergent (concentration of 2%) aqueous solution, then wash it in an ultrasonic cleaning machine for 5 minutes, and then ultrasonically wash it with distilled water for 5 minutes, wipe off the visible water on the surface with absorbent soft paper, and blow dry it with a hair dryer (power of 50 W) for 2.5 minutes, weigh it with an analytical balance (accuracy: 0.0001g) as the initial weight, recorded as M1 (mg), and determine the density of each sample according to the test method (water displacement method) specified in GB4472, which is used to calculate the volume loss of the sample (ρ=m / V) by the change in the sample weight. After each friction and wear test, the height of the 13 points calibrated on the surface of the specimen is measured with a digital micrometer. The specimen is placed at the position calibrated for the first measurement each time, and a digital mobile platform (with an accuracy of 1μm) is used to keep the displacement precision of the probe between each measurement point within ±1μm. The average height of the 13 measured points is taken as the specimen height, recorded as the initial height H1. For each specimen, after 800 wears, the specimen is cleaned, dried, and the specimen height is measured, recorded as H2. After the friction and wear experiment, the average wear height of the specimen is measured.
[0104] 2. Bending strength: Tested according to YY1042-2011 standard. Specifically, the sample was filled into a mold with a width of (2±0.1) mm × a thickness of (2±0.1) mm × a length of (25±0.1) mm. A dental hand-held curing lamp (power of 800 mW / cm 2 ), select high gear, divide into upper, middle and lower areas, irradiate each area for 40s, then demould, repeat the above steps to prepare 5 specimens, and then polish the surface with 2000 mesh sandpaper wet grinding, use a tensile testing machine, a three-point bending test is carried out under the conditions of a span of 20mm and a loading speed of (0.75±0.25)mm / min, and the average value of ten specimens is used for evaluation.
[0105] 3. Cure depth: Test according to YY1042-2011 standard. Specifically, place a piece of transparent PE film on a glass sheet, and then place the mold on the film. Fill the mold with the resin material to be tested (the mold is a cylindrical shape with a length of 6 mm and a diameter of 4 mm). During filling, the material slightly overflows the mold. Place a second piece of transparent PE film on top of the mold, and then place a second piece of glass on the film. Squeeze the mold and film between the glass sheets to remove excess material. Then place the mold on filter paper and remove the glass sheet covering the upper film. Dental handheld curing light (power 800mW / cm 2 ) The output window is against the film. Select high gear and irradiate for 60 seconds. After the irradiation is over, immediately remove the sample from the mold and remove the uncured material with a plastic scraper. Use a screw micrometer to test the height of the cured material to an accuracy of ±0.1mm, and then divide the test value by 2. This value is recorded as the curing depth.
[0106] 4. Hardness test: Shaw D was used for the test: the sample was filled into a mold with a width of (10±0.1) mm × a thickness of (2±0.1) mm × a length of (10±0.1) mm, covered with polyester film, and divided into 4 areas. A dental hand-held curing lamp (power of 800 mW / cm 2 ) Select high gear and irradiate for 40 seconds. During irradiation, the output window is against the partition of the film, and each partition is irradiated in turn. Place the cured resin block on the Shore D hardness tester, press down the handle, and read the reading immediately, which is the material hardness.
[0107] 5. Leveling test: Dip a small amount of sample with a disposable dental applicator stick, quickly apply a film on the base specimen in one direction, let it dry for 15 seconds, then put the specimen into the post-curing light box, cure it with medium and high light for 5 minutes, and observe whether there are brush marks on the surface. No brush marks visible to the naked eye, the edge can be leveled as Class A, slight brush marks, the edge can be leveled as Class B, obvious brush marks, the edge cannot be leveled as Class C.
[0108] 6. Viscosity test: Take 19g-22g sample and put it into the test stainless steel container of the viscometer. The liquid should cover the mark in the container. Select the appropriate rotor and speed for testing.
[0109] The test results of the above embodiments and comparative examples are shown in Table 5.
[0110] Table 5
[0111]
[0112] From Table 4, we can see the following points:
[0113] The wear test results of Examples 1-9, Comparative Examples 5-6 and Comparative Examples 1-3 show that the wear height of the photocurable resin is reduced after adding fillers, and the higher the content of fillers, the smaller the wear height, which indicates that the addition of fillers can effectively improve the wear resistance of photocurable resin.
[0114] Through the flexural strength and hardness test results of Examples 1-9, Comparative Examples 5-6 and Comparative Examples 1-3, it can be concluded that the hardness of the photocurable resin increases after adding fillers, and the higher the content of fillers, the greater the hardness of the photocurable resin. This shows that the addition of fillers can effectively improve the wear resistance of the photocurable resin.
[0115] Examples 15 to 16 changed the type of filler, from inorganic filler to organic filler, organic regenerated cellulose. The test results showed that the type of filler would affect the physical properties of the photocurable resin (such as flexural strength, hardness, wear height, etc.). Compared with organic fillers, the addition of inorganic fillers such as fumed silica and glass powder would increase the flexural strength and hardness of the photocurable resin, while increasing the wear resistance.
[0116] The difference between Examples 10-14 and Comparative Example 4 is the different types of polymerizable acrylate derivatives. By changing the type of polymerizable acrylate derivatives, the properties of the prepared resin composition are different. By comparing the results of Examples 10-14 and Comparative Example 4, it can be obtained that the optimal combination is Bis-GMA, TEGDMA and UDMA.
[0117] Through Comparative Example 6, it is found that when the filler content is too high, the viscosity of the resin composition will increase sharply, showing a gel state. At this time, the light-curing resin has poor leveling properties, and it is difficult to evenly apply it on the surface of the resin restoration during actual use, affecting the appearance.
[0118] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A resin composition, characterized in that According to mass fraction, the resin composition comprises: at least two polymerizable acrylate derivatives; at least one acrylate monomer; at least one photoinitiator; At least two fillers; The filler is a silane-modified filler; Based on 100 parts by mass of the resin composition, the mass of the filler is 2 to 30 parts.
2. The resin composition according to claim 1, characterized in that The polymerizable acrylate derivative has any one of a hydroxyl group, an amino group, or an isocyanate group, or a combination of at least two of them.
3. The resin composition according to claim 1 or 2, characterized in that Calculated by weight percentage, the resin composition comprises 50 to 70 parts of polymerizable acrylate derivatives, 10 to 30 parts of acrylate monomers, 1 to 5 parts of photoinitiators, and 2 to 30 parts of fillers.
4. The resin composition according to any one of claims 1 to 3, characterized in that The filler in the silane-modified filler includes an organic filler and / or an inorganic filler; Preferably, the organic filler comprises any one or a combination of at least two of regenerated cellulose, polyamide fiber, polymethyl methacrylate microspheres or ultra-high molecular weight polyethylene powder; Preferably, the inorganic filler comprises fumed silica and / or glass powder; Preferably, the particle size of the filler is 0.01-1 μm.
5. The resin composition according to any one of claims 1 to 4, characterized in that The resin composition further comprises at least one additive; Preferably, the additive includes any one or a combination of at least two of a co-initiator, a colorant or a defoamer; Preferably, the resin composition comprises 1 to 10 parts of additives in terms of mass percentage.
6. The resin composition according to any one of claims 1 to 5, characterized in that The photoinitiator has a molar extinction coefficient greater than 1000 at 365 nm or 405 nm.
7. A method for preparing the resin composition according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Silane-modified fillers are used to obtain silane-modified fillers; A polymerizable acrylate derivative, an acrylate monomer, a photoinitiator and a silane-modified filler are mixed to obtain a resin composition.
8. The preparation method according to claim 7, characterized in that: The silane modification comprises: mixing a solvent, a filler and a silane coupling agent, performing ultrasonic treatment, and then performing solid-liquid separation and drying in sequence to obtain the silane-modified filler; Preferably, the silane coupling agent includes any one or a combination of at least two of γ-aminopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane or N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane; Preferably, the silane coupling agent accounts for 0.1% to 15% of the mass of the filler.
9. A photocurable resin, characterized in that: The photocurable resin is obtained by photocuring the resin composition according to any one of claims 1 to 6.
10. Use of the resin composition according to any one of claims 1 to 6 in dental materials, or use of the photocurable resin according to claim 9 in dental materials.
Citation Information
Patent Citations
Photopolymerizable surface-coating material for dental use
JP1992029910A
Cited By
Modified resin slurry for 3D printing as well as preparation method and application of modified resin slurry
CN121343089A